Antibacterial photocatalytic activity of different crystalline TiO2 phases in oral multispecies biofilm - Pantaroto, Heloisa N.; Ricomini-Filho, Antonio P.; Bertolini, Martinna M.; Dias da Silva, José Humberto [UNESP]; Azevedo Neto, Nilton F. [UNESP]; Sukotjo, Cortino; Rangel, Elidiane C. [UNESP]; Barão, Valentim A.R. (Elsevier, 2018)
Objective: Titanium dioxide (TiO2) incorporation in biomaterials is a promising technology due to its photocatalytic and antibacterial activities. However, the antibacterial potential of different TiO2 crystalline structures on a multispecies oral biofilm remains unknown. We hypothesized that the different crystalline TiO2 phases present different photocatalytic and antibacterial activities. Methods: Three crystalline TiO2 films were deposited by magnetron sputtering on commercially pure titanium (cpTi), in order to obtain four groups: (1) machined cpTi (control); (2) A-TiO2 (anatase); (3) M-TiO2 (mixture of anatase and rutile); (4) R-TiO2 (rutile). The morphology, crystalline phase, chemical composition, hardness, elastic modulus and surface free energy of the surfaces were evaluated. The photocatalytic potential was assessed by methylene blue degradation assay. The antibacterial activity was evaluated on relevant oral bacteria, by using a multispecies biofilm (Streptococcus sanguinis, Actinomyces naeslundii and Fusobacterium nucleatum) formed on the treated titanium surfaces (16.5 h) followed by UV-A light exposure (1 h) to generate reactive oxygen species production. Results: All TiO2 films presented around 300 nm thickness and improved the hardness and elastic modulus of cpTi surfaces (p < 0.05). A-TiO2 and M-TiO2 films presented superior photocatalytic activity than R-TiO2 (p < 0.05). M-TiO2 revealed the greatest antibacterial activity followed by A-TiO2 (≈99.9% and 99% of bacterial reduction, respectively) (p < 0.001 vs. control). R-TiO2 had no antibacterial activity (p > 0.05 vs. control). Significance: This study brings new insights on the development of extra oral protocols for the photocatalytic activity of TiO2 in oral biofilm-associated disease. Anatase and mixture-TiO2 showed antibacterial activity on this oral bacterial biofilm, being promising surface coatings for dental implant components.
Keywords: Bacteria; Biofilms; Dental implants; Phototherapy; Sputtering; Titanium oxide